Jebakan ‘Harga Murah Semu’ Layanan Daring Pengantar Makanan Go-Food dan Grab Food - Putra Aditya Lapalelo (Jurnal Spektrum Komunikasi, 2022)
Delivery service applications such as Gojek and Grab in recent years have become part of the lives of urban people, becoming one of the instruments to fulfill the needs of urban consumers who are called "living in high mobility". Especially the online food delivery service GO-FOOD and GRAB FOOD which promise to fulfill the need for food delivery services at low prices, even with discounts that look fantastic. With all the intents and purposes, these two services are not only able to help solve the problem of "time" for urban residents who are too busy with their activities, but are also provided at low prices so that they are attractive and difficult to ignore. But with some observations, the cheap price of this food delivery service hides academic suspicions, Is it true that this lifestyle has no risk for urban residents?. This question makes a search to see what kind of lifestyle is behind the cheap consumption of this online food delivery service, an important topic to talk about. Especially with the current Covid-19 pandemic where the service business is crucial. This research uses a phenomenological study with observations and in-depth interviews with gojek and grab driver partners, business actors who partner with grab and gojek, to consumers in the Surabaya city area, and juxtaposed it with pop culture and consumer culture perspectives to provide a comprehensive picture of how consumers' lifestyles consume services. - this online service. As a result, it was found that cheap online delivery services and lots of discounts were just a “trap” for consumers. Consumers are being forced to live a “high cost consumption” lifestyle that is shrouded in the label of “low prices and discounts”.